Moderate-intensity exercise with blood flow restriction on cardiopulmonary kinetics and efficiency during a subsequent high-intensity exercise in young women : a cross-sectional study - Borges, Robson Fernando (2021)
Blood flow restriction (BFR) training applied prior to a subsequent exercise has been used as a method to induce changes in oxygen uptake pulmonary kinetics (V_ O2P) and exercise performance. However, the effects of a moderate-intensity training associated with BFR on a subsequent high-intensity exercise on V_ O2P and cardiac output (QT) kinetics, exercise tolerance, and efficiency remain unknown. This prospective physiologic study was performed at the Exercise Physiology Lab, University of Brasilia. Ten healthy females (mean ±SD values: age=21.3±2.2 years; height=1.6±0.07m, and weight=55.6±8.8 kg) underwent moderate-intensity training associated with or without BFR for 6 minutes prior to a maximal high-intensity exercise bout. V_ O2P, heart rate, and QT kinetics and gross efficiency were obtained during the high-intensity constant workload exercise test. No differences were observed in V_ O2P, heart rate, and QT kinetics in the subsequent high-intensity exercise following BFR training. However, exercise tolerance and gross efficiency were significantly greater after BFR (220±45 vs 136±30 seconds; P<.05, and 32.8±6.3 vs 27.1±5.4%; P<.05, respectively), which also resulted in lower oxygen cost (1382±227 vs 1695±305mLmin–1 ). We concluded that moderate-intensity BFR training implemented prior to a high-intensity protocol did not accelerate subsequent V_ O2P and QT kinetics, but it has the potential to improve both exercise tolerance and work efficiency at high workloads. Abbreviations: BFR = blood flow restriction, CWR = constant work rate, GE = gross efficiency, GET = gas exchange threshold, HR = heart rate, PE = priming exercise, QT = cardiac output kinetics, RIPC = remote ischemic preconditioning, VO_ 2P = pulmonary O2 uptake, VO_ 2peak = VO_ 2P at peak exercise.